On the kinetics of the Langmuir-type heterogeneous reactions - Skakauskas, Vladas; Katauskis, Pranas (Nonlinear Analysis: Modelling and Control, 2011)
In this paper we investigate three two-dimensional in space mathematical models of the kinetics of unimolecular heterogeneous reactions proceeding onto planar surfaces. All models include the diffusion of the reactant from a bounded vessel towards an adsorbent, adsorption of the molecules of the reactant, their desorption, conversion (reaction) of the adsorbate into a product, instantaneous product desorption, and the diffusion of the product from the adsorbent into the same vessel. One of these models is based on the Langmuir-type kinetics of the surface reactions, the other one is based on the local steady-state value of the surface coverage, and the last one, in addition to the first model, involves the diffusion of the adsorbate along the adsorbent. Diffusivity of all species is assumed to be constant. Models were solved numerically by using the finite difference technique. By changing input parameters the effects of the rate constants of the reactant adsorption, desorption, and reaction and the influence of the surface diffusion of the adsorbate and approximation of the surface coverage by its steady-state value on the kinetics of surface reactions were studied numerically.